Practical tips and tricks in measuring strain, strain rate and twist for the left and right ventricles - Christopher Johnson; Katherine Kuyt; David Oxborough; Martin Stout (Echo Research and Practice, 2019)
Strain imaging provides an accessible, feasible and non-invasive technique to assess cardiac mechanics. Speckle tracking echocardiography (STE) is the primary modality with the utility for detection of subclinical ventricular dysfunction. Investigation and adoption of this technique has increased significantly in both the research and clinical environment. It is therefore important to provide information to guide the sonographer on the production of valid and reproducible data. The focus of this review is to (1) describe cardiac physiology and mechanics relevant to strain imaging, (2) discuss the concepts of strain imaging and STE and (3) provide a practical guide for the investigation and interpretation of cardiac mechanics using STE.